Gene Action and Combining Ability Analysis for Seed Yield and Component Traits in Castor Genotypes - Versha Sharma; Sita Ram Kumhar; Motilal Mehriya; Ramesh Chand Meena; Ramesh (Annals of Arid Zone, 2024)
General and specific combining ability was studied in castor genotypes under three different environments at Mandor, Jodhpur using three lines and ten testers along with their resultant 30 hybrids and one check (GCH-8) for seed yield and yield attributing traits. Analysis of variance showed significant influence on gca (general combining ability) and sca (specific combining ability) variances for most of the characters studied. Tester MCP-1-1 was found good general combiner for seed yield at 120, 150, 180 and 210 days after sowing and for other yield determining traits. On the contrary, two testers viz., MP-12-17 and MP-27-17 were found superior for overall seed yield at final harvest done at 210 days after sowing and also for some yield governing traits. Hybrids possessing high sca effects for overall seed yield were SKP-84 × MP-36-17, MCP-1-1 × MP-12-17 and DPC-15 × MP-34-17, these hybrids were found promising for high seed yield in arid regions of Rajasthan.